Structural equation modeling of organizational silence and bullying on employees turnover willingness(The case: selected governmental organizations in Ahvaz) - mahdi naddaf; farajollah rahimi; zahra hadizade (پژوهش‌های روانشناختی در مدیریت, 2016)
This study is an attempt to study the effect of organizational silence and bullying on the willingness of employees to turnover. The method of this study, according to its purpose is an applied research and due to data collection, is a descriptive research of correlational-causative one. The study population is a selection among Ahvaz governmental organizations' staff and regarding limited population formula a sample size of 326 people have been selected. For data collection and measurement of variables a questionnaire was used. In order to analyze data and test hypotheses Pearson correlation coefficient using SPSS software and structural equation modeling using AMOS software were utilized. The results showed that organizational silence has a significant and positive impact on bullying employees, organizational silence has also positive and significant impact on bullying. The results of this study did not verified bullying impact on the willingness of employees to turnover. However, its mediating role between organizational silence and bullying was significant.